Characterization of the resistance mechanism against BYDV-PAV in maize - Schmidt, Maria; Will, Torsten; Ruckwied, Britta; Habekuß, Antje; Stich, Benjamin (Frontiers in Agronomy, 2025)
Arthropods threaten crop production by feeding on plants and, most importantly, by transmitting viruses. BYDV-PAV is the most prevalent virus species that causes barley yellow dwarf disease, one of the most economically important viral diseases affecting cereals worldwide. Maize plays a central role in BYDV-PAV epidemiology, serving as a “green bridge” for BYDV-PAV and its vector Rhopalosiphum padi in summer. Some studies have reported that the incidence of persistently transmitted viruses may be reduced in plants that are resistant to their insect vectors. In contrast, the choice test applied in our study revealed that R. padi is not repelled by the included BYDV-PAV-resistant maize inbreds. Significant differences in phloem architecture observed among the inbreds suggested that aphids feeding on BYDV-PAV-resistant maize may have difficulties reaching the phloem or establishing a stable feeding site. However, monitoring of aphid feeding behavior using the electrical penetration graph technique on maize inbreds that differed in their BYDV-PAV susceptibility revealed no correlation between R. padi feeding and BYDV-PAV resistance. Furthermore, we could not confirm the generation of reactive oxygen species (ROS), a typical reaction of plants during aphid infestation and infection of some viruses. In summary, we conclude that the BYDV-PAV resistance mechanisms in maize act directly on the virus and not on its vector, R. padi.